2017
DOI: 10.1108/nfs-10-2016-0154
|View full text |Cite
|
Sign up to set email alerts
|

The effect of various cooking methods on resistant starch content of foods

Abstract: Purpose Resistant starch, defined as all starch and starch-degradation products not absorbed by small intestine of healthy individuals, is included in the diet of individuals due to its prebiotic characteristics and protective effects against diseases like colon cancer, type II diabetes, obesity and cardiovascular diseases. Some cooking methods are known as effective on resistant starch content of foods. The purpose of this paper is to explore the effect of various cooking methods on resistant starch content o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 55 publications
2
21
0
1
Order By: Relevance
“…The differences found between the reported values and the one obtained in the present study can be given by several factors, among them, the methods and the processing variables. According to Eroglu and Buyuktuncer [64], the shorter residence time in extrusion cooking may offer fewer opportunities for amylose chains to associate, which causes a reduction in the resistant starch content, while a longer residence time may provide more opportunities for the association of the amylose chain.…”
Section: Resultsmentioning
confidence: 99%
“…The differences found between the reported values and the one obtained in the present study can be given by several factors, among them, the methods and the processing variables. According to Eroglu and Buyuktuncer [64], the shorter residence time in extrusion cooking may offer fewer opportunities for amylose chains to associate, which causes a reduction in the resistant starch content, while a longer residence time may provide more opportunities for the association of the amylose chain.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that some cooking methods, such as steaming, baking and autoclave cooking led to an increase in the amount of resistant starch in the food. On the other hand, other forms of cooking such as pressure cooking led to a decrease in the resistant starch content in the food, whereas methods such as frying, microwaving, boiling and extrusion cooking affect the starch in different ways depending on the starch source and the conditions present during processing (Elif and Zehra 2017). The techniques employed to process starch, such as temperature, extrusion and tempering have varying effects on the resistant starch present in a food, consequently having varied physiological effects in the body.…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
“…The RS degree of formation in food depends on the type of starch contained and adopted processing conditions, such as water content, pH, heating temperature and time, number of heating and cooling cycles, freezing, and drying. It is also influenced by the duration and storage conditions [17][18][19]. Moreover, Eroglu and Buyuktuncer [19] reported that cooking methods like steaming, baking, and autoclave cooking increased the amount of RS in food, whereas pressure cooking was found to decrease the amount of RS in food.…”
Section: Resistant Starch (Rs)mentioning
confidence: 99%
“…It is also influenced by the duration and storage conditions [17][18][19]. Moreover, Eroglu and Buyuktuncer [19] reported that cooking methods like steaming, baking, and autoclave cooking increased the amount of RS in food, whereas pressure cooking was found to decrease the amount of RS in food. Cooking methods, such as boiling, microwave heating, extrusion, and frying, have the potential to increase the amount of RS, depending on the source of starch and processing conditions.…”
Section: Resistant Starch (Rs)mentioning
confidence: 99%